Hubungan Antara Tingkat Pendidikan dan Pemahaman Manajemen Lembaga Pendidikan Islam dengan Kinerja Kepala Raudhatul Athfal Muslimat Kabupaten Klaten - Barokah, Anisatul (Universitas Nusantara PGRI Kediri, 2020)
This research aims at determining the relationship between: 1) education level with headmaster performance of Raudhatul Athfal Muslimat; 2) understanding of Islamic educational institutions management with headmaster performance of Raudhatul Athfal Muslimat; 3) education level and understanding of Islamic educational institutions management with headmaster performance of Raudhatul Athfal Muslimat. The method used was quantitative correlation. This research was conducted at Raudhatul Athfal Muslimat Klaten. The population in this research were all headmasters of Raudhatul Athfal Muslimat Klaten totaling 44 people. The sample in this research used total sampling. Technique data collection was questionnaire. Test of the validity used product moment formula, while the instrument reliability test using Cronbach alpha formula. Data analysis techniques used were correlation analysis that began with the prerequisite test consisting of normality, linearity, and the significance of regression. This research concludes that: 1) There is a correlation between education level with headmaster performance of Raudhatul Athfal Muslimat (r count = 0.728 > r table = 0.297); 2) There is a correlation between understanding of Islamic educational institutions management with headmaster performance of Raudhatul Athfal Muslimat (r count = 0.442 > r table = 0.297); 3) There is a correlation between education level and understanding of Islamic educational institutions management with headmaster performance of Raudhatul Athfal Muslimat (F count = 29,600 > F table = 3.23) R12 = 0.769 >r table= 0.297. This means that better education level creates better headmaster performance of Raudhatul Athfal Muslimat, and better understanding of Islamic educational institutions management creates better the headmaster performance of Raudhatul Athfal Muslimat.